2005
DOI: 10.1002/mnfr.200400086
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the epidermal growth factor receptor in apple juice extract

Abstract: The polyphenol-rich extract of a consumer-relevant apple juice blend was found to potently inhibit the growth of the human colon cancer cell line HT29 in vitro. The epidermal growth factor receptor (EGFR) and its subsequent signaling cascade play an important role in the regulation of cell proliferation in HT29 cells. The protein tyrosine kinase activity of an EGFR preparation was effectively inhibited by the polyphenol-rich apple juice extract. Treatment of intact cells with this extract resulted in the suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(110 citation statements)
references
References 30 publications
(27 reference statements)
7
100
0
3
Order By: Relevance
“…The action of tannic acid is specific to CXCL12/ CXCR4 given that other chemokines/chemoattractants are not effected by this tannin preparation (70). Furthermore, apple tannins block Fc R1/IgE binding (55) and prevent epidermal growth factor signaling, presumably through physically blocking the receptor (57). Similar polyphenols from tea bind CD11b on monocytes, which we recently found for APP as well (43).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The action of tannic acid is specific to CXCL12/ CXCR4 given that other chemokines/chemoattractants are not effected by this tannin preparation (70). Furthermore, apple tannins block Fc R1/IgE binding (55) and prevent epidermal growth factor signaling, presumably through physically blocking the receptor (57). Similar polyphenols from tea bind CD11b on monocytes, which we recently found for APP as well (43).…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, these illnesses are commonly associated with ␥␦ T cell regulatory activities (7,(51)(52)(53)(54), suggesting the described immunostimulatory properties of the Cat's Claw plant could be partially due to the activation of ␥␦ T cells. Preparations containing the apple-condensed tannins we described are also recognized for similar immunostimulatory properties (49,(55)(56)(57). These observations on the immunological effects of Cat's Claw and apple tannins support the prospect for condensed tannins to be used as a therapy to increase ␥␦ T cell function in innate immunity and wound healing.…”
Section: Discussionmentioning
confidence: 55%
“…They concluded that IQ is a promising antioxidant agent but that it did not inhibit Caco2 cellular growth [79] . In 2005, Kern et al [80] reported a perspective on the antiproliferative effect and demonstrated the potent EGFRinhibitory properties of polyphenolrich apple juice extract in adenocarcinoma colon in vitro model (HT29) [80] . Another study suggested that the beneficial effects of red wine on human health were attributable to the flavonoid content, which channeled the body metabolism towards Omethylation to yield compounds with potential protective effects against cancer [81] .…”
Section: Colon Cancermentioning
confidence: 99%
“…[40][41][42] Esse aumento do consumo de maçãs pode ser atribuído, praticamente, a dois fatores: por ser um alimento de acesso fácil à população e, aos benefícios que esse alimento proporciona à saúde humana. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Entretanto, as pesquisas recentes revelam que as maçãs, principalmente as comercializadas e consumidas in natura, expõem as pessoas que as consomem, aumentando os riscos de contaminação por resíduos de agrotóxicos, podendo afetar diretamente a saúde. [58][59][60][61][62][63][64][65][66][67] Embora alguns resíduos de agrotóxicos encontrados nesses alimentos não excedam os limites máximos permitidos para o consumo humano, ainda não se conhecem exatamente os efeitos da acumulação, ao longo do tempo, desses compostos no organismo.…”
Section: Introductionunclassified